Влияние осадков на разрешающую способность радиолокационной станции по угловым координатам - Путятин, В.Г.; Корбан, Д.В.; Князь, А.И. (Реєстрація, зберігання і обробка даних, 2017)
Проведен анализ влияния выпадающего дождя на разрешающую способность судовой радиолокационной станции (РЛС) по угловым координатам, работающую в миллиметровом и сантиметровом диапазонах длин волн. Показано, что в сантиметровом диапазоне длин волн (λ = 3 см...10 см) имеет место улучшение разрешающей способности судовой РЛС по угловым координатам, а в миллиметровом диапазоне длин волн имеет место как улучшение разрешающей способности судовой РЛС поугловым координатам, так и ее ухудшение. Проведено аналіз впливу випадного дощу на роздільну здатність суднової радіолокаційної станції (РЛС) за кутовими координатами, яка працює в міліметровому та сантиметровому діапазонах довжин хвиль. Показано, що в сантиметровому діапазоні довжин хвиль (λ = 3 см…10 см) має місце поліпшення роздільної здатності суднової РЛС за кутовими координатами, а в міліметровому діапазоні довжин хвиль має місце як поліпшення роздільної здатності суднової РЛС за кутовими координатами, так і її погіршення. The study of precipitation on the resolution power of marine radar by angular coordinates, antenna which radiates a linear-polarized electromagnetic wave of millimeter and centimeter ranges has been provided. The interaction of the wave with particles of precipitation presented in the form of a power wave from the effective surface of the scattering reflective volume of rain is taken into account. The effective surface of scattering and attenuation on all particle sizes in the dropdown of rain on the way is found. It was found that for the centimeter wavelength range (λ = 3 cm...10 cm) attenuation is much higher than the scattering. The resulting conditions to improve the resolution of the antenna of marine radar by angular coordinates are in the centimeter wavelength range. In the millimeter range of wavelengths occurs as the improvement of the resolution capability of the antenna of marine radar and its deterioration depending on the intensity of precipitation.